Stories of Hegemony: The Political Stakes of the Rise and Decline of US Power. Issue 4 (13th December 2016) - Biswas, Shampa
Abstract : With Asia as its backdrop, Alfred McCoy's paper gives us a story of the rise of US hegemony after World War II. Using "military bases" rather than wars as a metric of imperial power, the paper traces the geopolitics of imperial expansion (and sometimes retraction) through a close and rich study of the many contestations around US military presence in the Philippines—contestations that occurred in both the United States and the Philippines. In doing so, one of the paper's most profound insights, made with considerable archival documentation, is that colonization and decolonization do not follow a linear trajectory and that its politics, rather than a simple imposition from the colonizer onto the colonized, are instead quite messy, complicated, and perhaps mostly importantly, in a constant state of negotiation. Thus, for instance, the paper shows us that political independence is not a clear rupture from colonization to decolonization, that arguments for the continuation or discontinuation of imperial relations post-independence are complex on both sides of the imperial divide and shift in different directions over time, and that who appears as a "threat" or an "enemy" that mobilizes a national community and nationalist resistance is also complex and inconstant. In other words, McCoy provides us with a historically detailed story of the rise of US hegemony in the latter half of the twentieth century through an account of the complex expansion of the US presence in Asia.